Investigating sirukumab for rheumatoid arthritis: 2-year results from the phase III SIRROUND-D study. Issue 2 (16th November 2018) - Thorne, Carter; Takeuchi, Tsutomu; Karpouzas, George Athanasios; Sheng, Shihong; Kurrasch, Regina; Fei, Kaiyin; Hsu, Benjamin
Abstract : Objectives: The phase III, multicentre, randomised, double-blind, placebo-controlled, parallel-group SIRROUND-D study evaluated long-term efficacy and safety of the interleukin (IL)-6 inhibitor, sirukumab, in patients with active rheumatoid arthritis (RA) refractory to disease-modifying antirheumatic drugs (DMARDs). Methods: Patients were randomised 1:1:1 to sirukumab 100 mg every 2 weeks (q2w), 50 mg every 4 weeks or placebo q2w subcutaneously. Patients initially randomised to placebo were rerandomised at Weeks 18, 40 or 52 to one of the sirukumab groups until Week 104. Results: Of 1670 randomised patients, 1402 were included in the full analysis set and 1269 in the radiographic analysis set at Week 104. American College of Rheumatology scores, Disease Activity Score based on C-reactive protein, Clinical Disease Activity Index and clinically meaningful improvements in patient-reported outcomes were sustained at Week 104 among patients initially randomised to sirukumab. Placebo patients subsequently rerandomised to sirukumab showed clinical improvements at Week 104 that were comparable to results among patients initially randomised to sirukumab. Radiographic progression from Week 52 to Week 104 was comparable between all groups whether initially randomised to sirukumab or subsequently rerandomised to sirukumab from placebo. No new safety signals were identified in the extended exposure period compared with the initial 52 weeks of treatment. Conclusions: Sirukumab treatment resulted in sustained reductions in clinical signs and symptoms and minimal progression in radiographic damage over 2 years among patients with RA refractory to DMARDs. The safety profile of sirukumab was as expected for an anti-IL-6 agent, with no new signals reported.